Maladaptive behaviours of maternal orphans in high schools of Tshwane North of Gauteng, South Africa - Thembi V. Khoza; Mathildah M. Mokgatle (African Journal of Primary Health Care & Family Medicine, 2023)
Background: Some orphaned adolescents find it difficult to cope and adjust to the loss of a mother. Studies to explore specific adjustment challenges experienced by this vulnerable group, are necessitated by the growing need to inform support services for orphans.